COMPARATIVE ANALYSIS OF CARBON EMISSION DISCLOSURE BASED ON GRI 305 IN COAL MINING COMPANIES - Nabilah Iffat Arianti; Gugus Irianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
The dynamics between regulatory compliance and market orientation create complexity in carbon accounting practices. This study analyzes carbon emission disclosure strategies based on GRI 305 at PT Bukit Asam Tbk (PTBA) and PT Adaro Andalan Indonesia Tbk (AADI). Using a comparative case study method on the 2024 Sustainability Reports, this research examines how differences in ownership status influence reporting patterns. The results indicate that PTBA applies strategic readability through detailed technical disclosures to fulfill regulatory legitimacy, whereas AADI adopts a green catering approach aligned with market signaling. Despite their differing approaches, both entities demonstrate a pattern of greenhushing, characterized by minimal quantitative information on downstream Scope 3 emissions. It is concluded that reporting strategies prioritize legitimacy fulfillment and market responsiveness over comprehensive value chain transparency.